Hemolysis, Elevated Liver Enzymes, and Low Platelets, Severe Fetal Growth Restriction, Postpartum Subarachnoid Hemorrhage, and Craniotomy: A Rare Case Report and Systematic Review - Shadi Rezai; Justin Faye; Alexander Hughes; Mon-Lai Cheung; Joel R. Cohen; Judy A. Kaia; Paul N. Fuller; Cassandra E. Henderson (Case Reports in Obstetrics and Gynecology)
Introduction. Hemolysis, elevated liver enzymes, and low platelets (HELLP) syndrome is a relatively uncommon but traumatic condition occurring in the later stage of pregnancy as a complication of severe preeclampsia or eclampsia. Prompt brain computed tomography (CT) or magnetic resonance imaging (MRI) and a multidisciplinary management approach are required to improve perinatal outcome. Case. A 37-year-old, Gravida 6, Para 1-0-4-1, Hispanic female with a history of chronic hypertension presented at 26 weeks and 6 days of gestational age. She was noted to have hemolysis, elevated liver enzymes, and low platelets (HELLP) syndrome accompanied by fetal growth restriction (FGR), during ultrasound evaluation, warranting premature delivery. The infant was delivered in stable condition suffering no permanent neurological deficit. Conclusion. HELLP syndrome is an uncommon and traumatic obstetric event which can lead to neurological deficits if not managed in a responsive and rapid manner. The central aggravating factor seems to be hypertension induced preeclamptic or eclamptic episode and complications thereof. The syndrome itself is manifested by hemolytic anemia, increased liver enzymes, and decreasing platelet counts with a majority of neurological defects resulting from hemorrhagic stroke or subarachnoid hemorrhage (SAH). To minimize adverse perinatal outcomes, obstetric management of this medical complication must include rapid clinical assessment, diagnostic examination, and neurosurgery consultation.